Dental Satisfaction and Its Effect on Oral Health- Related Quality of Life in Patients Referred to Bushehr Health Centers - Safari, Sina; Bahrami Maleki, Hamed; Bazooband, Mona; Karimi Afshar, Marzieh; Atashpareh, Neshat; Heidaripour, Kianoush (Journal of Dental School, 2025)
Objective(s): Oral health-related quality of life (OHRQoL) is widely used to assess how oral conditions influence both individuals and communities. The purpose of this study was to examine patients’ satisfaction with dental appearance and its association with OHRQoL. Methods: This cross-sectional survey included 400 patients who visited dental clinics in Bushehr, Iran. Information was obtained through a questionnaire covering demographics, perceptions of dental aesthetics, Oral Health Impact Profile-14 (OHIP-14) scale, and clinical dental findings. Data analysis was performed using Chi-square, independent t-test, linear regression, and ANOVA with a significance level set at p<0.05. Results: Among participants, 41.5% were male, with a mean age of 34.78 ± 12.14 years. Most participants had a diploma (37.5%), and reported a moderate economic status (52%). The mean scores for dental aesthetic satisfaction and OHRQoL were 10.10 ± 4.50 and 13.60 ± 4.50, respectively. No significant gender differences were observed. A significant positive correlation was found between satisfaction with teeth and OHRQoL (p < 0.001). Conclusion: The highest satisfaction was related to smile appearance (53.5%), while the lowest was with tooth color (31%). Satisfaction with teeth was significantly associated with better OHRQoL, emphasizing the importance of dental aesthetics in overall well-being.